On leveraging e-services for effective relationship management: exploring the necessary technological components - Galbreath, Jeremy; Hoffman, D. (Inderscience Enterprises Limited, 2007)
This paper is the collaborative effort between a former IT practitioner and a services marketing academician. Its primary purpose is to provide an overview of the e-service technologies that enable effective Relationship Management (RM). To do so, a framework is introduced that consists of ‘front’ and ‘back’ office technologies. By exploring a front and back office context, this paper simplifies the technological complexity of e-services and offers insight into how firms can more effectively manage their relationship assets.